University proceedings. Volga region. Social sciences - O.L. Lushnikova (Известия высших учебных заведений. Поволжский регион: Общественные науки)
Background. The issue of preserving a contemporary countryside isn’t new. This problem has been actively discussed among the scientific community for several decades. The main focus on economic issues related to labor and employment problems, unemploy-ment, standard and quality of life, etc. The preserving of the population depends on level of economic development. Therefore demographic issues are also being investigated: natural movement population, migration processes. However, the difficult socio-economic situation of rural areas also has deeper and irreversible processes – the loss of the cultural identity of rural society, which is especially important for national countryside. Different processes as decline of the population of such countryside, the loss of traditional way of life among local ethnic groups of region, the reduction of traditional area, the decrease of Khakass language, disappearance of original crafts, etc. This issue is the subject of study in cultural geography. The one analyses within the framework of the theory of cultural landscape. The focus of this article is the problem of preserving the national countryside (using the example of Khakassia). Materials and methods. The article is based on population census data, and the study also used the results of the author’s surveys in 2018 (n = 486), 2020 (n = 1050) and 2022 (n = 404). Results. The author analyzes the dynamics of the number of the titular eth-nic group of the republic, marital and reproductive behavior, the number of speakers of the Khakass language, and traditional economic activities. Conclusions. The numerical minori-ty of the titular ethnic group, the low activity of the marital and reproductive behavior of the Khakass people, an nationally mixed marriages, a decrease in the number of speakers of their native language, low interest in livestock as a traditional form of economic activity and other factors don’t allow us to make an optimistic forecast about the preserving of the Khakass countryside for the near future.